Evaluation of a Fully Automatic Measurement of Short-Term Variability of Repolarization on Intracardiac Electrograms in the Chronic Atrioventricular Block Dog - Smoczyńska, Agnieszka; Sprenkeler, David J.; Aranda, Alfonso; Beekman, Jet D.M.; Bossu, Alexandre; Dunnink, Albert; Wijers, Sofieke C.; Stegemann, Berthold; Meine, Mathias; Vos, Marc A. (Frontiers in Physiology, 2020)
Background: Short-term variability (STV) of repolarization of the monophasic action potential duration (MAPD) or activation recovery interval (ARI) on the intracardiac electrogram (EGM) increases abruptly prior to the occurrence of ventricular arrhythmias in the chronic AV-block (CAVB) dog model. Therefore, this parameter might be suitable for continuous monitoring of imminent arrhythmias using the EGM stored on an implanted device. However, 24/7 monitoring would require automatic STVARI measurement by the device. Objective: To evaluate a newly developed automatic measurement of STVARI for prediction of dofetilide-induced torsade de pointes (TdP) arrhythmias in the CAVB-dog. Methods: Two retrospective analyses were done on data from recently performed dog experiments. (1) In seven anesthetized CAVB-dogs, the new automatic STVARI method was compared with the gold standard STVMAPD at baseline and after dofetilide administration (0.025 mg/kg in 5 min). (2) The predictive value of the automatic method was compared to currently used STVARI methods, i.e., slope method and fiducial segment averaging (FSA) method, in 11 inducible (≥3 TdP arrhythmias) and 10 non-inducible CAVB-dogs. Results: (1) The automatic measurement of STVARI had good correlation with STVMAPD (r2 = 0.89; p < 0.001). Bland-Altman analysis showed a small bias of 0.06 ms with limits of agreement between −0.63 and 0.76 ms. (2) STVARI of all three methods was significantly different between inducible and non-inducible dogs after dofetilide. The automatic method showed the highest predictive performance with an area under the ROC-curve of 0.93, compared to 0.85 and 0.87 of the slope and FSA methods, respectively. With a threshold of STV set at 1.69 ms, STVARI measured with the automatic method had a sensitivity of 0.91 and specificity of 0.90 in differentiating inducible from non-inducible subjects. Conclusion: We developed a fully-automatic method for measurement of STVARI on the intracardiac EGM that can accurately predict the occurrence of ventricular arrhythmias in the CAVB-dog. Future integration of this method into implantable devices could provide the opportunity for 24/7 monitoring of arrhythmic risk.